Matters of justice : Pueblos, the judiciary, and agrarian reform in revolutionary Mexico - Baitenmann, Helga (Mexican experience., 2020)
"Helga Baitenmann offers a novel interpretation of Mexico's revolutionary agrarian reform, an unconstitutional takeover by the executive of the judiciary's authority over contentious land matters, and examines the role that villagers played in shaping post-revolutionary state formation by siding with the executive branch over the judiciary"--